THE ROLE OF ARTIFICIAL INTELLIGENCE IN ENHANCING WRITING MOTIVATION AMONG EFL STUDENTS (Global Conference on Multidisciplinary Research and Innovation, 2026)
Motivation is a critical factor in the success of English as a Foreign Language (EFL) writing instruction, yet many students struggle with anxiety, lack of immediate feedback, and low self-efficacy. The integration of Artificial Intelligence (AI) tools such as automated writing evaluation, chatbots, and generative language models offers new possibilities for enhancing writing motivation. This article explores the role of AI in addressing common motivational barriers, examining how AI-driven features like real-time feedback, personalized prompts, and non-judgmental interaction can foster intrinsic motivation, reduce writing apprehension, and increase learner engagement. Practical strategies for integrating AI into the EFL writing classroom are also provided.
Keywords: Artificial Intelligence, writing motivation, EFL students, automated feedback, learner engagement, teaching strategies.